Implementing green innovations and ecodesign in companies : differences among the Nordic textile and IT sectors - Salo, Hanna (My University, 2019)
The thesis examines the differences and similarities of green innovation and ecodesign and how they are implemented in textile and IT companies that manufacture and/or design products in the Nordic countries. Green innovations are defined as an approach of developing and implementing product, process, marketing, organisational or institutional innovations that reduce environmental impact in relation to a stated common reference. Ecodesign is a collaborative, proactive and systematic design and management process that integrates environmental issues into product development processes. The thesis looks at innovative targets and mechanisms and their level of radicality to compare the two approaches. It applies this framework in the context of the Nordic countries, which are perceived as forerunners in environmental matters. The thesis uses mixed methods to form a general overview of the current situation of green innovation and ecodesign implementation: first a broad questionnaire and second, deepening the understanding by interviewing forerunning companies. The questionnaire was conducted in Webropol and sent by the national industrial associations and the researcher to the target population (N=104). Thereafter, six Finnish companies were interviewed. Textiles and IT were chosen to be the target sectors due to concerns about their global environmental impacts. The findings of this thesis can be summarised into three propositions: 1) Green innovations concern more varied targets than ecodesign by looking at both the technological and non-technological issues. 2) The respondents are fairly mature in terms of how they integrated environmental sustainability into their operations. The main stimulus for environmental proactivity is general willingness, whereas many companies are deterred by cost increases and societal barriers. 3) Companies remain focused on technical product and process innovations and especially functional innovations are lagging behind. The contribution of this study to existing literature on green innovations and ecodesign is its promotion of understanding of how companies can participate in the required systemic change towards a circular economy. The study indicates the main contributors for green innovations in the product design phase. This thesis suggests that research and development activities related to environmental matters and the use of ecodesign tools to support the information base and communication purposes are very central to the creation and implementation of innovations.
Keywords: green innovation, ecodesign, companies, circular economy, tools, Nordic countries, textile, IT sector